Production economics of high-quality microalgae. Issue 5 (4th May 2017) - Demirbas, Ayhan
ABSTRACT: The aim of this study is to investigate the microalgae production technologies and production costs. Biofuels production costs can vary widely by feedstock, conversion process, scale of production, and region. Microalgae will become the most important biofuel source in the near future. Microalgae are unique photosynthetic organisms given that they accumulate storage lipids in substantial quantities and thrive in high-salinity water. Photosynthetic growth requires light, carbon dioxide (CO2 ), water, and inorganic salts. Temperature must remain generally within 20–30°C. During photosynthesis, algae use solar energy to fix CO2 into algal biomass, so the water used to cultivate algae must be enriched with CO2 . Microalgae can potentially be employed for the production of biofuels in an economically effective and environmentally sustainable manner.